2020
DOI: 10.1080/17421772.2020.1846768
|View full text |Cite
|
Sign up to set email alerts
|

Regional economic resilience in the European Union: a numerical general equilibrium analysis

Abstract: Using a spatial general equilibrium model, this paper investigates the resilience of European Union regions under three alternative recessionary shocks, each activating different economic adjustments and mechanisms. We measure the vulnerability, resistance and recoverability of regions and identify key regional features affecting the ability of regions to withstand and recover from unexpected external shocks. The analysis reveals that the responses of regions vary according to the nature of the external distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Research on urban economic resilience has received more attention [ 18 ]. Di Pietro et al measured the vulnerability, resistance and recoverability of regions to discuss the resilience and identify key regional features [ 19 ]. Islam et al found that severe adverse impact of the pandemic on global production, employment, and prices [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on urban economic resilience has received more attention [ 18 ]. Di Pietro et al measured the vulnerability, resistance and recoverability of regions to discuss the resilience and identify key regional features [ 19 ]. Islam et al found that severe adverse impact of the pandemic on global production, employment, and prices [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They investigate various factors of economic resilience. For example, Pietro et al (2020), using an equilibrium model, demonstrate that the stability of economic systems depends on the nature of the external shock and characteristics of the economy itself, such as capital and labour intensity, openness, and specialization. The authors also highlight the importance of innovation, agglomeration effects, and education factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a small CGE literature that complements case studies and econometric work in the analysis of regional resilience. Di Pietro et al (2020) use the RHOMOLO CGE model to identify the differential resilience of individual NUTS 2 (European Nomenclature of Territorial Units for Statistics at level two) regions to EU-wide temporary demand and supply shocks, focusing on the role of industrial and trade structure. On a smaller scale, Rose (2004) discusses CGE as 'a state of art tool' for the analysis of the behaviour of individual regions in response to adverse, focused supply-side shocks, such as natural disasters.…”
Section: Regional Resiliencementioning
confidence: 99%
“…There is a small CGE literature that complements case studies and econometric work in the analysis of regional resilience. Di Pietro et al. (2020) use the RHOMOLO CGE model to identify the differential resilience of individual NUTS 2 (European Nomenclature of Territorial Units for Statistics at level two) regions to EU-wide temporary demand and supply shocks, focusing on the role of industrial and trade structure.…”
Section: Regional Resiliencementioning
confidence: 99%